1982
DOI: 10.1007/bf00729446
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation in chicken by the use of irradiated male gametes

Abstract: Genetic transformation for egg and feather colour hs been obtained in the whole animal, chicken, by the use of irradiated male gametes. In this technique recipient females are first inseminated with irradiated semen from the donor and 24 h later are reinseminated with unirradiated, normal semen of the recipient strain. The transformed progeny are identical to the female strain but for one or a few genes derived from the irradiated semen. The expression of the transferred gene is irregular and may occur either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The results presented here confirm those of Pandey and Patchell (1982) in suggesting that, whether by -66 pseudofertilisation or by another mechanism, genetic material from lethally irradiated sperm -becomes incorporated into otherwise normally fertilised embryos. The presence of the haplotypes of both normal parents in addition to that from the irradiated sperm precludes the possibility that either a fraction of the irradiated sperm remained -2-3 fertile or that the parental lines were contaminated -2-0 or incorrectly mated.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results presented here confirm those of Pandey and Patchell (1982) in suggesting that, whether by -66 pseudofertilisation or by another mechanism, genetic material from lethally irradiated sperm -becomes incorporated into otherwise normally fertilised embryos. The presence of the haplotypes of both normal parents in addition to that from the irradiated sperm precludes the possibility that either a fraction of the irradiated sperm remained -2-3 fertile or that the parental lines were contaminated -2-0 or incorrectly mated.…”
Section: Discussionsupporting
confidence: 81%
“…Following the protocol of Pandey and Patchell (1982) birds were inseminated twice weekly (Mondays and Thursdays) with irradiated semen. The hens received normal semen on Tuesdays and Fridays.…”
Section: Inseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was argued that irradiated spermatozoa might similarly provide novel genetic material for incorporation into the zygote when fertilisation by a normal sperm took place. With the use of feather and egg colour as markers Pandey and Patchell (1982) showed that chicks expressed these markers at a frequency of 3.5%.…”
Section: Methods For Gene Transfermentioning
confidence: 99%
“…The procedures, when better understood, have the potential of not only considerably expediting plant, and possibly animal (Pandey, 1980c;Pandey and Patchell, 1982) breeding but also producing desirable recombinants which could not be produced before because of close linkage between desirable and undesirable genes, or because of inviability of the normal hybrid zygotes or complete sterility of the normal hybrids.…”
Section: Introductionmentioning
confidence: 99%